1991
DOI: 10.1111/j.1365-2621.1991.tb14627.x
|View full text |Cite
|
Sign up to set email alerts
|

Twin‐Screw Extrusion Texturization of Acid and Alkali Denatured Soy Proteins

Abstract: Effect of pH on functional characteristics of soy protein was investigated by modifying soy flour through acid (HCI) or alkali (NaOH) addition. Acid-and alkali-treated proteins were evaluated and texturized by twin-screw extrusion. Products were analyzed by rheological, functional, and ultrastructural methods. Acid-modified texturized protein had little expansion, increased peak force, increased work of shearing, and a nonoriented fiber arrangement. Slightly alkaline extrudates had increased rehydration but po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 13 publications
2
17
0
1
Order By: Relevance
“…WHC is mostly in¯uenced by protein±water interactions, water±water interactions and physical capillary actions. 16 Probably the greater WHC of the extruded samples was due to a primarily physical retention of water by capillary action in the new structure formed by aggregation of proteins These results are consistent with those of Narayana and Narasinga Rao, 36 Bencini 37 and Gujska and Khan 29 with other bean¯ours. The water solubility indices of both extruded peas and kidney beans increased signi®cantly with respect to the raw seeds.…”
Section: Whc Wsi and Oacsupporting
confidence: 93%
“…WHC is mostly in¯uenced by protein±water interactions, water±water interactions and physical capillary actions. 16 Probably the greater WHC of the extruded samples was due to a primarily physical retention of water by capillary action in the new structure formed by aggregation of proteins These results are consistent with those of Narayana and Narasinga Rao, 36 Bencini 37 and Gujska and Khan 29 with other bean¯ours. The water solubility indices of both extruded peas and kidney beans increased signi®cantly with respect to the raw seeds.…”
Section: Whc Wsi and Oacsupporting
confidence: 93%
“…However, WPs with a higher degree of aggregation were found to have increased viscosity due to the aggregates greater effective volume which could entrap more water than the individual WP molecules (Firebaugh, 2004). These findings are similar to those of texturized soy protein studied by Dahl and Villota (1991) and Fleming, Sosulski, Kilara, and Humbert (1974). Their results indicated that the viscosity of soy proteins increased markedly after proteins were modified by the alkaline treatment.…”
Section: Apparent Viscositysupporting
confidence: 91%
“…The effects of pH modifications during extrusion process on WP reactivity and functionality of final products have been reported (Amaya-Llano et al, 2007;Dahl and Villota, 1991;Martinez-Serna and Villota, 1992;Onwulata et al, 2006;Law and Leaver, 2000;Monahan et al, 1995;Walsh and Carpenter, 2001). Their studies showed that conformations and protein-protein interactions of WPs were strongly affected by pH.…”
Section: Introductionmentioning
confidence: 91%
“…The tWPC samples exhibited the ability to impart a wide range of viscosities by varying protein concentrations. This corresponds to stronger protein-protein and hydrodynamic interactions among particles with an increase in solids in the system (Dahl and Villota, 1991).…”
Section: Apparent Viscositymentioning
confidence: 98%
See 1 more Smart Citation